LEARNING LOSS: WHY IS COLLABORATION BETWEEN EDUCATORS AND PARENTS IMPORTANT? - Rediani, Ni Nyoman; Kaize, Bernadetha Risky (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2023)
The condition of learning loss has already occurred or been experienced by students in suburban or rural areas. While it cannot be denied that this phenomenon also occurs in urban areas, its frequency is not as high as in suburban and rural regions. This research is conducted in the form of an ex-post facto study, which means data collection is carried out after the event being studied has occurred. The subjects of this research involve 15 teachers, comprising 2 civil servants (PNS) and 13 contract teachers (honorer). Grade 5 has a total of 20 students with diverse abilities. The data collection methods used in this research include observation, interviews, questionnaires, and tests. The analytical technique applied in this study is based on the assumption of linearity using regression linearity testing. The research results indicate a significant influence between the roles of educators and parents in addressing learning loss, as indicated by significance values smaller than 0.05. Furthermore, the calculation results show that the combined influence of the variables of educators' and parents' roles is 0.879. The inactivity of educators and parents in the learning process can lead to learning loss, which in turn negatively impacts the quality of education. Therefore, effective communication, collaboration, cooperation, and coordination are necessary to ensure that the education process remains of high quality.